Experiencing Organizational Change During an Era of Reform: Police Scotland, Narratives of Localism, and Perceptions from the 'Frontline'. (6th August 2018) - Fyfe, Nicholas R; Anderson, Simon; Bland, Nick; Goulding, Amy; Mitchell, James; Reid, Susan
Abstract: In 2011, the Scottish Government took the decision to create a single, national police force, reconfiguring a structure of regional police forces, which had prevailed since the 19th century. Despite a strong narrative around localism in the legislation establishing Police Scotland, the new force that was established in 2013 quickly found itself at the centre of a debate around an emerging 'crisis of localism' as critics expressed concerns over the centralization of decision-making and a lack of sensitivity to local contexts. Drawing on qualitative research carried out in four communities across Scotland in 2016, the analysis presented in this article examines the experience of organizational change from the perspective of officers in local policing teams and from local stakeholders. The analysis is structured around the strategic aims of reform of improved local service delivery, more equal local access to specialist expertise, and enhanced connections with local communities. The article highlights the sense of exclusion from the decision-making surrounding the organizational changes associated with the implementation of reform experienced by local, rank-and-file officers.